Halal Transaction: Implication For Digital Retail By Using Financial Technology - Yolanda Masnita; Mangku Rasyawal; Husna Leila Yusran (Jurnal Ilmiah Ekonomi Islam, 2021)
Digital transaction is an important marketing discipline concept, for companies and consumers. The purpose of this conceptual article is to investigate the application of halal in online trading transactions that use payments with financial technology - Fintech. This article is based on a review of literature based on Islamic sharia and marketing literature which provides a discussion of online transactions and fintech as a way to develop understanding of Muslim business. It was concluded that buying and selling is a halal activity as long as it meets the shariah requirements. The difference between online business and offline business in Islam is the transaction process (contract). Online transactions are permissible according to Islam as long as they do not contain elements that can damage them such as usury, tyranny, fraud, fraud and the like and fulfill the terms and conditions of the sale and purchase. Included in the completion of the transaction that is payment using fintech becomes halal, as long as according to Islamic shariah guidance. The practical implications of this research for companies that use online transactions, it is important to expand the concept of halal in the direction of payment. Effective alignment is required between halal policies, payment strategies and the buying process. Companies that use online transactions can develop in three stages, from seeing halal compliance as an opportunity, making a halal payment system, to making the whole buying and selling process halal certified